Multiple Shooting and Time Domain Decomposition Methods: MuS-TDD, Heidelberg, May 6-8, 2013 - Carraro, Thomas; Geiger, Michael; Körkel, Stefan; Rannacher, Rolf (Contributions in mathematical and computational sciences, 2015)
T. Akman et al: Space-Time Discontinuous Galerkin Methods for Optimal Control Problems Governed by Time Dependent Diffusion-Convection-Reaction Equations -- Th. Carraro et al: Direct and Indirect Multiple Shooting for Parabolic Optimal Control Problems -- M.J. Gander: 50 Years of Time Parallel Time Integration -- S. Grötschel et al: Reducing Memory Requirements in Scientific Computing and Optimal Control -- Y. Hasegawa: Optimal Control of Heat and Fluid Flow for Efficient Energy Utilization -- D. Janka et al: Direct Multiple Shooting for Optimum Experimental Design -- D. Kaschek et al: A Unified Approach to Integration and Optimization of Parametric Ordinary Differential Equations -- R. Kircheis et al: Parameter Estimation for PDAE Constrained Models Using a Reduced Approach -- M. Klinger: A Variational Approach for Physically Based Image Interpolation Across Boundaries -- C. Kreutz et al: Statistics for Model Calibration -- A. Potschka: Direct Multiple Shooting for Parabolic PDE Constrained Optimization -- R. Quirynen et al: Multiple Shooting in a Microsecond -- Th. Richter et al: Time Discretizations of Fluid-Structure Interactions -- St. Ulbrich: Preconditioners Based on 'Parareal' Time-Domain Decomposition for Time-Dependent PDE-Constrained Optimization -- E. Kostina et al: Direct Multiple Shooting for Optimization Problems in ODE Models -- M. Schlick: Parareal Time-Stepping for Limit-Cycle Computation of the Incompressible Navier-Stokes Equations with Uncertain Periodic Dynamics